2008
DOI: 10.1186/1478-4491-6-30
|View full text |Cite
|
Sign up to set email alerts
|

A strategy to improve skills in pharmaceutical supply management in East Africa: the regional technical resource collaboration for pharmaceutical management

Abstract: BackgroundInternational initiatives such as the Global Fund to Fight AIDS, Tuberculosis and Malaria, the President's Emergency Plan for AIDS Relief and the President's Malaria Initiative have significantly increased availability and access to medicines in some parts of the developing world. Despite this, however, skills remain limited on quantifying needs for medications and ordering, receiving and storing medications appropriately; recording medications inventories accurately; distributing medications for use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 10 publications
0
22
1
Order By: Relevance
“…Overall, CAA antibiotics are indicated for use in 75% (9/11) of indications by body systems with the respiratory, genitourinary and musculoskeletal disorder systems having the most indications for CAA antibiotics. The wide number of indications of CAA antibiotics by level of healthcare and disease is a risk factor for overuse and the development of AMR, with misuse linked to limited prescriber and diagnostic capacity as well as pressure from patients . In Namibia, with the current human resource issues, nurses are the main prescribers at the lower levels of care, eg, PHCs, where antibiotic prescribing is mainly empiric.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Overall, CAA antibiotics are indicated for use in 75% (9/11) of indications by body systems with the respiratory, genitourinary and musculoskeletal disorder systems having the most indications for CAA antibiotics. The wide number of indications of CAA antibiotics by level of healthcare and disease is a risk factor for overuse and the development of AMR, with misuse linked to limited prescriber and diagnostic capacity as well as pressure from patients . In Namibia, with the current human resource issues, nurses are the main prescribers at the lower levels of care, eg, PHCs, where antibiotic prescribing is mainly empiric.…”
Section: Discussionmentioning
confidence: 56%
“…One of the factors driving increased prescribing of antibiotics in Namibia is the burden of infectious diseases particularly HIV/AIDS, which may well aggravate resistance to essential antibiotics . Of concern are the primary healthcare centres (PHC) with gaps in laboratory diagnostics, education regarding appropriate antibiotic use and human capacity . Among PHCs, the risk of antibiotic misuse is exacerbated by the high workload for health workers with limited training on antibiotic pharmacotherapy as recommended by WHO and Medicines and related Act of Namibia .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the later study the main reason was insufficient deliveries of medicines from the regional medical stores. Taken together, these findings emphasize the need to build capacity of drug store managers for quantification and forecasting of medicines through provision of continuing education and professional development 22 .…”
Section: Discussionmentioning
confidence: 75%
“…This could mean that whatever little training is done may be having little impact. Related studies have previously indicated weaknesses in training in aspects of pharmaceutical management and suggested strengthening in service training of different cadres of health workers (Matowe et al, 2008;Waako et al, 2009).…”
Section: In-service Trainingmentioning
confidence: 99%